2015
DOI: 10.1590/0102-37722015042577481490
|View full text |Cite
|
Sign up to set email alerts
|

Rorschach: Normas para Adolescentes em Diferentes Etapas da Vida

Abstract: RESUMO Trata-se de estudo do método de Rorschach para construção de normas para adolescentes, com 118 participantes da cidade de São Paulo, com idades entre 13 e 17 anos. Foram realizados: estatística descritiva do Rorschach e estudos por meio de ANCOVA e ANOVA - com e sem a mediação da variável "complexidade" (R-PAS), para comparar adolescentes de 13-14 com 15-17 anos e a amostra de adolescentes com uma amostra de estudo normativo de adultos. Nos procedimentos com idades dicotomizadas, encontrou-se apenas uma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Some authors question the temporal stability of the variables (Parker, Hanson & Hunsley, 1988;West, 1998), while others emphasize this as a strength (Exner & Andronikof-Sanglade, 1992;Gronnerod, 2004;Weiner, 2004). This method is typically used to evaluate psychotherapeutic change in an adult population (Bram, 2010;Heedea et al, 2009;Nascimento, 2001;Weiner & Exner, 1991). In the current study, the Rorschach revealed improvements in the cognitive triad of the patient, in her interpersonal relations and in her ability to regulate affect, relational experience and interpersonal expression of emotion.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors question the temporal stability of the variables (Parker, Hanson & Hunsley, 1988;West, 1998), while others emphasize this as a strength (Exner & Andronikof-Sanglade, 1992;Gronnerod, 2004;Weiner, 2004). This method is typically used to evaluate psychotherapeutic change in an adult population (Bram, 2010;Heedea et al, 2009;Nascimento, 2001;Weiner & Exner, 1991). In the current study, the Rorschach revealed improvements in the cognitive triad of the patient, in her interpersonal relations and in her ability to regulate affect, relational experience and interpersonal expression of emotion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the psychological functioning of these individuals, as well as their respective personal adaptation skills, demand analysis within their specific social, educational, occupational, family and interpersonal contexts. Therefore, even though Rorschach testing is considered a method that is free from culture, it is also sensitive to cultural differences because it captures the modes of expression inherent to the individuals, which demands familiarity of the evaluator with the culture of that specific individual being assessed in order to seek an appropriate interpretation of the test (Nascimento, 2010). The relevance of studies with the objective to develop normative references of the Rorschach method per regions and specific stages of human development, therefore follows.…”
Section: Discussionmentioning
confidence: 99%
“…Palabras clave: test de Rorschach, normas de test, adolescentes, técnicas proyectivas, personalidad 1 Paper derived from the doctoral dissertation of the primary author under the supervision of the second author, defended in 2011, in the Graduate Program in Psychology at Faculdade de Filosofia, Ciências e Letras de Ribeirão Preto of the Universidade de São Paulo. structure and functioning of individuals is practically incontestable (Azoulay et al, 2007;Hisatugo & Yazigi, 2014;Ikiz et al, 2010;Mihura et al, 2013;Nascimento, 2010;Pasian & Loureiro, 2010;Viglione, Meyer, Mihura, Erard, & Erdberg, 2012;Weiner, 1998Weiner, /2000Yazigi, 2014). The Rorschach test method helps access conscious and observable characteristics of personality but also reviews repressed and unconscious aspects (Rausch de Traubenberg, 1970.…”
Section: Estudio Normativo Del Rorschach (Escuela De Paris) Para Adolmentioning
confidence: 99%
See 1 more Smart Citation